Literature Review: Analysis of Cyanogenic Compounds in Plants - Noli, Zozy Aneloi; Asih, Enda Tarni; Pasha, Gusti Ari Afrilya; Siagian, Marhamah; Adelia, Sabbrina; Putri, Suci Indah; Santoso, Putra (Jurnal Biologi Tropis, 2025)
Cyanogenic glycosides are hydrocarbon compounds that can bind to CN groups and sugars. Certain plants, notably higher plants, can perform cyanogenesis, forming cyanogenic glycosides as by-products of biochemical reactions. From a medical perspective, cyanide is known to negatively impact health, particularly the respiratory system, as it binds oxygen in the blood to toxic compounds. Symptoms of cyanide poisoning from food consumption include dizziness, weakness, vomiting, throat inflammation, and abdominal cramps. Acute poisoning and death have been reported from consuming food containing 50 – 100 mg of cyanide. This review utilizes a literature study method, focusing on national journals from the past decade accessed via Google Scholar. The findings identify five plant species containing cyanogenic glycosides: cassava, bamboo shoots, cassava leaves, raw Pangium edule seeds, and Dioscorea hispida tubers. Cassava, in particular, contains linamarin, a cyanogenic glycoside found in all parts of the plant, with bitter varieties generally having higher toxin levels.